PENGARUH EMPLOYEE INVOLVEMENT, JOB DESIGN, DAN FLEXIBLE WORK ARRANGEMENT TERHADAP MOTIVASI KERJA KARYAWAN PT ABM INVESTAMA TBK JAKARTA DI MASA PANDEMI COVID-19 - Nia Safitri, (2022)
Abstract This research uses quantitative methods to determine the effect of employee involvement, job design, and flexible work arrangement on motivation objectively and systematically. This study uses the object of employees of PT ABM Investama Tbk Jakarta during the Covid-19 pandemic. The sample used is a saturated sample of 86 people. Data were collected through questionnaires distributed to employees of PT ABM Investama Tbk Jakarta using the google form application. Testing of the data in this study using the SmartPLS 3.0 test application. The series of test processes carried out resulted in the conclusion that 1) there was a positive and significant influence on employee involvement on motivation, 2) there was a positive and significant influence on job design on motivation, 3) flexible work arrangement had a positive and significant effect on motivation. Keywords: employee involvement, job design, flexible work arrangement, motivation.